2019
DOI: 10.1093/mnras/stz3121
|View full text |Cite
|
Sign up to set email alerts
|

A Correlation in the Waiting-time Distributions of Solar Flares

Abstract: In isolated solar active regions, we find that the waiting times between flares correlate with flare magnitudes as determined by the GOES soft X-ray fluxes. A "build-up and release" scenario (BUR) for magnetic energy storage in the solar corona suggests the existence of such a relationship, relating the slowly varying subphotospheric energy sources to the sudden coronal energy releases of flares and CMEs. Substantial amounts of research effort had not previously found any obvious observational evidence for suc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
2
6
2
Order By: Relevance
“…The new search of GOES flare statistics for the largest sunspot groups of Cycle 24 has not revealed the existence of a correlation between flare magnitude and the waiting time until the next flare, thought to reveal a mechanism in which a reservoir (containing free magnetic energy, for example) releases random amounts of its content at a prescribed threshold level. This contradicts the earlier finding (Hudson, 2020) of such a correlation, apparently present in two isolated regions. The weakness and intermittency of any such correlation means that it has no application to the prediction of flare properties, unlike the case of the pulsar PSR J0537-6910, for which Middleditch et al (2006) found a precise predictive capability.…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…The new search of GOES flare statistics for the largest sunspot groups of Cycle 24 has not revealed the existence of a correlation between flare magnitude and the waiting time until the next flare, thought to reveal a mechanism in which a reservoir (containing free magnetic energy, for example) releases random amounts of its content at a prescribed threshold level. This contradicts the earlier finding (Hudson, 2020) of such a correlation, apparently present in two isolated regions. The weakness and intermittency of any such correlation means that it has no application to the prediction of flare properties, unlike the case of the pulsar PSR J0537-6910, for which Middleditch et al (2006) found a precise predictive capability.…”
Section: Discussioncontrasting
confidence: 98%
“…The behavior here differs from that found by Hudson (2020) in at least two ways. First, NOAA 12673 was distinctly not an isolated group, suggesting that the coronal environment of this region has not masked its BUR behavior.…”
Section: Specific Regionscontrasting
confidence: 99%
See 3 more Smart Citations